(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
For any country that chooses the direction of market economy, it is important to set up business activities correctly and its sustainable growth. Because today, the basis of the economy of many developed and developing countries of the world lies in properly organized business activities. State support is important for sustainable growth of business activity. This research paper examines the directions of state support of entrepreneurship and its legal basis in Uzbekistan.